Manpower training center for the handicapped - Morales, Nataniel M. (Manila : National University, 1998)
This proposal entitled 'Manpower training center for the handicapped" is study of structure that will house various needs of the handicapped persons and the requirements for the construction of housing and workshop of this proposal.